Qualitative Analysis of Inpatient Prisoner Patient Satisfaction at Hospital X in 2025 - Syientia Wit Gantara (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
Patient satisfaction is the level of feeling that arises from comparing the health services received with the patient’s expectations of those services. This study aims to determine the perception of inpatient prisoner patient satisfaction at Sartika Asih Hospital in 2025. The factors influencing prisoner patient satisfaction were analyzed based on five dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangible evidence. This study used a qualitative design to understand the phenomena experienced by the research subjects, including behavior, perceptions, motivation, and actions. The informants in this study consisted of five people: one nurse, one head nurse, one policy maker, and two prisoner patients. Data were collected through in-depth interviews, while data processing and validation were carried out using triangulation techniques. The results showed that all informants expressed satisfaction with the services provided by Sartika Asih Hospital. The dimensions of reliability, responsiveness, and assurance were rated good, the empathy dimension was rated very good, while the tangible dimension was rated fairly good. The conclusion of this study indicates that health services for inpatient prisoner patients have generally been implemented well; however, improvements are still needed in the facilities and infrastructure of the prisoner ward. It is recommended that Sartika Asih Hospital improve Police Medicine services (DOKPOL), conduct wound care training, pay attention to the safety and welfare of nursing staff such as salaries and health insurance, enhance communication between the hospital and the police, strengthen the vigilance of police and hospital officers in guarding prisoner patients, and improve the quality of facilities and infrastructure in the prisoner care room.